Tuning the stereoselectivity of a DNA-catalyzed Michael addition through covalent modification - Dey, Surjendu; Jäschke, Andres (Angewandte Chemie. International edition, 2015)
Complexes of G-quadruplex DNA and CuII ions have previously been applied as catalysts in asymmetric reactions, but the largely unspecific and noncovalent nature of the interaction has impeded understanding of the structural basis of catalysis. To better control the formation of a catalytically competent species, DNA quadruplexes were derivatized with linker-bpy-CuII complexes in a site-specific manner and applied in asymmetric aqueous Michael additions. These modified quadruplexes exhibited high rate acceleration and stereoselectivity. Different factors were found to be important for the catalytic performance of the modified G-quadruplexes, among them, the position of modification, the topology of the quadruplex, the nature of the ligand, and the length of the linker between the ligand and DNA. Moving the same ligand by just two nucleotides inverted the stereochemical outcome: quadruplexes modified at position 10 formed the (−)-enantiomer with up to 92 % ee, while DNA derivatized at position 12 formed the (+)-enantiomer with up to 75 % ee. This stereopreference was maintained when applied to structurally different Michael acceptors. This work demonstrates a new and simple way to tune the stereoselectivity in DNA-based asymmetric catalysis.